Integrating vocational rehabilitation and mental healthcare to improve the return-to-work process for people on sick leave with stress-related disorders: results from a randomized trial - Hoff, Andreas; Fisker, Jonas; Poulsen, Rie Mandrup; Hjorthøj, Carsten; Rosenberg, Nicole Kristjansen; Nordentoft, Mads; Bojesen, Anders Bo; Eplov, Lene Falgaard (Scandinavian Journal of Work, Environment & Health, 2022)
' ' OBJECTIVE ': 'Stress-related disorders are common, associated with substantial individual suffering, and place a large economic burden on society. While treatment appears to be able to reduce symptoms, evidence of interventions to improve vocational outcomes is flimsy. Lack of integration of vocational rehabilitation and healthcare services has been suspected to be a major potential barrier in return-to-work (RTW) processes; therefore, we aimed to test the effectiveness of such integration. ' ' METHODS ': 'We randomized participants who were on sick leave for ≥ 4 weeks with a stress-related disorder. They were allocated to (i) service as usual (SAU), (ii) improved mental healthcare (MHC), or (iii) integrated interventions (INT). The primary outcome was RTW rates measured at 12 months. Secondary outcome were RTW rates measured at 6 months, proportion in work at 12 months, and levels of stress, anxiety, depression, and functioning at 6 months. ' ' RESULTS ': 'We included 666 participants. On the primary outcome and almost all other vocational outcomes, SAU was superior to both INT and MHC. MHC and INT did not differ on any vocational outcome. On several symptom scales, MHC showed lower values than SAU, whilst INT did not differ from the two other groups. ' ' CONCLUSION ': 'Both the INT and the MHC intervention lowered RTW rates compared with SAU, and thereby yielded a worse outcome. However, the MHC group showed a tendency towards having lower symptom levels compared with those in the SAU group; accordingly, the SAU group is not unequivocally superior. MHC and INT showed no general differences.
Keywords: adjustment disorder; common mental disorder; distress; exhaustion disorder; integrated service; mental healthcare; randomized trial; return to work; return-to-work; sick leave; stepped care; stress; stress-related disorder; vocational rehabilitation